2001
DOI: 10.1111/0447-2778.00021
|View full text |Cite
|
Sign up to set email alerts
|

A Crossnational Prediction Model for Business Success

Abstract: In this study, the Lussier (1995) success prediction model, originally developed using U.S. data, is tested using a sample of firms from Central Eastern Europe. The same factors found to be predictors of success in the U.S. (staffing, education level, use of professional advice, and planning) were also predictors of success and failure in Central Eastern Europe. All these factors have to do with the firm's human resources. These findings should lead to reconsideration of preconceptions existing in Central East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
1
41

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(204 citation statements)
references
References 12 publications
8
154
1
41
Order By: Relevance
“…(Blanchflower y Oswald, 1998;Lussier y Pfeifer, 2001). De acuerdo con Kibler et al (2011), los adultos mayores enfrentan las mismas dificultades para conseguir recursos financieros en comparación con emprendedores más jóvenes.…”
Section: Las Asimetrías De Condiciones Entre Adultos Mayores Y Jóveneunclassified
“…(Blanchflower y Oswald, 1998;Lussier y Pfeifer, 2001). De acuerdo con Kibler et al (2011), los adultos mayores enfrentan las mismas dificultades para conseguir recursos financieros en comparación con emprendedores más jóvenes.…”
Section: Las Asimetrías De Condiciones Entre Adultos Mayores Y Jóveneunclassified
“…Studies (Lussier, Pfeifer 2001;Lussier, Halabi 2010) have indicated that non-financial failure predictors in developed countries are the same as in developing ones, although it is not clear whether similar failed firms in different environments witness the same predictors. Despite remarkable similarities being found for financial predictors of failure in different environments (see e.g.…”
Section: Prior Failure Studiesmentioning
confidence: 99%
“…Despite the existing literature explaining the reasons for small business success; theories, concepts and practices developed in different contexts are not necessarily applicable to FELDA case. Moreover, scholars argue that the determinants of business success should be based on the context of research study is made, as they may be different from one context to the other (Lussier & Pfeifer, 2001). In this line of argument, Yunus, Aris, Abdul Majid, and Md.…”
Section: Introductionmentioning
confidence: 99%